Patterns and clinical presentation of Foreign Bodies in ENT among Sudanese Children in Khartoum state hospitals. - Rana Ahmed Abdelrahman Nasir; Sharfi Abdelgadir Omer Ahmed; Ibrahim Gaffar Ibrahim (Sudan Journal of Medical Sciences)
Abstract: -